Two Conflicting Concepts of the Right to Culture in the Colombian Constitution - Charria García, Fernando (DIXI, 2018)
Purpose: The present work explores the concept of culture in both the Universal Declaration of Human Rights of 1948 and the Colombian Constitution of 1991, in light of the conception of body of constitutional law. These references could have nothing particular, except that they are two different ways of expressing the concept of culture, which gives rise to a tense/relaxed relationship between the Colombian Constitution of 1991 and the Declaration of Human Rights of 1948. Description: As it is only natural, it is essential to resolve this tension from a legal perspective through an analysis and an interpretive study of the two concepts of culture. Point of view: This paper offers a type of interpretation that intends to provide the judge with an impression that can be used when dealing with this matter. Conclusions: To date, this concept has not been considered by any of the high judicial courts in Colombia, particularly the Constitutional Court, which is in charge of interpreting and controlling constitutional rules.